2022
DOI: 10.21294/1814-4861-2021-20-6-41-54
|View full text |Cite
|
Sign up to set email alerts
|

GLAD-PCR assay of DNA methylation sites in regulatory regions of some tumor-suppressor genes in breast cancer

Abstract: Hypermethylation of the RcgY sites is shown for many cancer diseases. such aberrant methylation, suppressing the gene activity, occurs at early stages of carcinogenesis. Recently, using glad-pcR assay, we have detected aberrantly methylated RcgY sites, which can be considered to be epigenetic markers of colorectal, lung, and gastric cancers. in breast cancer, methylation of the regulatory regions of ALX4, BMP2, CCND2, CDH13, CDX1, FOXA1, GALR1, GATA5, GREM1, HIC1, HMX2, HS3ST2, HOXC10, ICAM5, LAMA1, RARB, RASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, Schulten et al (2015) showed that RXRG was significantly upregulated in follicular FVPTCs of papillary thyroid carcinoma. Smetannikova et al (2019) reported that results of differential expression in DNA samples from lung cancer versus normal lung tissue showed that RXRG had high sensitivity and specificity and possessed good diagnostic potential. This is consistent with our findings, indicating that RXRG is essential in the advancement of SKCM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Schulten et al (2015) showed that RXRG was significantly upregulated in follicular FVPTCs of papillary thyroid carcinoma. Smetannikova et al (2019) reported that results of differential expression in DNA samples from lung cancer versus normal lung tissue showed that RXRG had high sensitivity and specificity and possessed good diagnostic potential. This is consistent with our findings, indicating that RXRG is essential in the advancement of SKCM.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Clinicopathological features included in this study should be further comprehensively summarized and (2) the possible mechanism, which suggested that the abnormal expression of PAX9 in CC may be correlated with the methylation, [35][36][37] can only be further explored in the follow-up research due to the limited time and funds.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that PAX9, possibly via inhibiting the proliferation and accelerating the apoptosis of tumor cells, can inhibit the growth of tumor. However, this study still has some limitations: (1) Clinicopathological features included in this study should be further comprehensively summarized and (2) the possible mechanism, which suggested that the abnormal expression of PAX9 in CC may be correlated with the methylation, 35–37 can only be further explored in the follow‐up research due to the limited time and funds.…”
Section: Discussionmentioning
confidence: 99%